Collaborative workplace writing: insights from experienced workplace writers / Latisha Asmaak Shafie and Surina Nayan - Shafie, Latisha Asmaak; Nayan, Surina (Universiti Teknologi MARA, Perlis, 2018)
Collaborative workplace writing is a collective writing that combines the expertise of a group of workplace writers to produce well- written pieces of writing. It is more efficient than single-author writing at workplaces. However, collaborative workplace writing is challenging as the writers have their challenges, schedules and aspirations. Therefore, insights from experienced collaborative workplace writers assist novice workplace writers who do not know what to expect when they write collaboratively. The study is a qualitative multiple case study to investigate the collaborative workplace writing skills and collaborative technologies used by four experienced collaborative workplace writers. The data were collected were collected through semi-structured interview. The study investigates the characteristics of experienced collaborative writers, the collaborative writing skills and the collaborative technologies. The findings suggested that experienced collaborative writers are subject matter experts, independent learners, 21st - century learning skills and adaptability skills. Additionally, the findings show that collaborative writers use a framework for collaborative writing in their writing projects. The study also reveals that collaborative technologies are necessities to enrich the writers’ collaborative writing